Educación y comunicación en el Menón de Platón - Pascual, Fernando (Alpha Omega, 2014)
Summary: Plato’s Meno offers important elements of his educational theory. This article begins with a brief introduction to this work, and then presents an analysis of several ideas that appear throughout it, with a special emphasis on those dealing directly or indirectly with the central theme of education and human communication. The article concludes with a summary of the work’s main arguments.Sommario: Il Menone offre importanti riflessioni sulla teoria educativa di Platone, e a queste è dedicato il presente lavoro. Dopo aver delineato una breve introduzione all’opera, varie idee che appaiono nel corso delle discussioni vengono analizzate, con particolare attenzione a quelle che toccano direttamente o indirettamente, tematiche su educazione e comunicazione. Infine, si sviluppa una sintesi dei principali argomenti considerati.